La història, creadora de mites - Nemes, Krisztina (Acta Hispanica, 2013)
Literary survival of a catalan miners’town in Aragonia sunk by Franco’s decision under the waves of the Ebro. The collective memory of its community works as a source of inspiration and of oral history for its chronicler, himself too son of the town. Only memory can keep alive the town after its death and the writer, responsible of collecting and registering it does a brilliant job. The inspired literary reconstruction of the town is represented as a broken mirror, reflecting more than one aspect of each person and event from different angles, thus offering the readers a perfectly authentic though fictional source of history, that of a compromised eyewitness.